Transformasi praktik akuntansi Usaha Mikro, Kecil, Menengah (UMKM): dari memori ke catatan - Dian Syariati; Unti Ludigdo; Ali Djamhuri (Jurnal Akuntansi Aktual, 2020)
Research on the accounting practices of micro, small and medium enterprises (SMEs) in Indonesia shows the failed implementation of accounting standards by SMEs. Since accounting practice is determined by internal and external factors that surround it and small firm is a unique entity, this research finding is interesting to be studied further by understanding accounting practiced by SMEs. Accounting may practice in the other form that further explains the "low" of SMEs accounting practice. This study uses transcendental phenomenology to understand SMEs accounting practice. Informant of this research is the owner of SMEs manufacturing business. Manufacturing enterprises are selected with consideration of the complexity of the business leading to a greater need for accounting practices. The results show the existence of an evolution of accounting practices. Accounting after tasks delegation was practiced in the note prior to practiced in the memories. Task delegation is the motivation for accounting practice evolution and fairness is value contained.